Aggressiveness of Ralstonia solanacearum isolates on Tomato - Chandrashekara, K N; Prasanna Kumar, M K; Saroja, S (Journal of Experimental Sciences, 2013)
Bacterial wilt caused by Ralstonia solanacearum is the world’s most economically important destructive disease of crop plants. Fifty seven isolates of R. solanacearum causing wilt on different host plants were collected from different agro climatic zones of India of which 54 isolates were confirmed as race-1, biovar-3 and 3 isolates as race-1, biovar-3B based on morphological, physiological, biochemical and pathogenicity studies. All the isolates were authenticated as Ralstonia solanacearum by using two sets of primers (OLI1 & Y2 and Y1 & Y2). Serological identity of the isolates was done by using diagnostic kit obtained from International Potato Research Center, Lima, Peru and single chain variable fragment antibody specific to Ralstonia solanacearum. Fifty seven isolates of R. solanacearum were inoculated on tomato (Solanum Lycopersicum L) cv. Avinash-II under artificial conditions at bacterial concentration of 5x108 cfu/ml to test its aggressiveness; the results obtained are discussed in this paper.